KESADARAN LINGKUNGAN DALAM PEMBELAJARAN BIOLOGI: TINJAUAN PUSTAKA SISTEMATIS - Puspa, Shynta Ayinda; Kusnadi, Kusnadi; Nurjhani, Mimin (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
Environmental awareness is a crucial competency in 21st-century biology education, yet teacher-centered learning practices, limited field experience, and limited assessment remain barriers. This study aims to map international publication trends related to environmental awareness, identify effective learning models, and evaluate approaches used at various levels of education. The method used was a systematic literature review in accordance with PRISMA guidelines, analyzing 19 Scopus-indexed articles (Q1–Q3) from 2021–2025 that examined levels from elementary school to university. The study results indicate a predominance of quasi-experimental and mixed methods approaches, a primary focus on elementary school and university, and research concentrations in Indonesia, Asia, and Europe. Effective learning models include Ethno-STEM, narrative, visual arts, robotics, and technology integration, with several studies emphasizing the use of local wisdom to strengthen students' ecological relevance and pro-environmental behavior. This approach has been shown to improve students' pro-environmental knowledge, attitudes, and behavior. The findings highlight the need to strengthen active, experiential learning, integrate Education for Sustainable Development (ESD) into the biology curriculum, and incorporate contextual, locally-based teaching strategies. The research provides an evidence map and recommendations for the development of evidence-based modules, learning strategies, and teacher training. ABSTRAK Kesadaran lingkungan menjadi kompetensi penting dalam pendidikan biologi abad ke-21, namun praktik pembelajaran yang berpusat pada guru, minim pengalaman lapangan, dan penilaian terbatas masih menjadi hambatan. Penelitian ini bertujuan memetakan tren publikasi internasional terkait kesadaran lingkungan, mengidentifikasi model pembelajaran efektif, serta mengevaluasi pendekatan yang digunakan dalam berbagai jenjang pendidikan. Metode yang diterapkan adalah tinjauan pustaka sistematis sesuai pedoman PRISMA, dengan analisis 19 artikel terindeks Scopus (Q1–Q3) tahun 2021–2025 yang meneliti jenjang SD hingga perguruan tinggi. Hasil kajian menunjukkan dominasi metode quasi-eksperimen dan mixed methods, fokus utama pada sekolah dasar dan perguruan tinggi, serta konsentrasi penelitian di Indonesia, Asia, dan Eropa. Model pembelajaran efektif meliputi Ethno-STEM, narasi, seni visual, robotika, serta integrasi teknologi, dengan beberapa studi menekankan penggunaan kearifan lokal untuk memperkuat relevansi ekologis dan perilaku pro-lingkungan peserta didik. Pendekatan ini terbukti meningkatkan pengetahuan, sikap, dan perilaku pro-lingkungan peserta didik. Temuan menegaskan perlunya penguatan pembelajaran aktif berbasis pengalaman, integrasi Education for Sustainable Development (ESD) dalam kurikulum biologi, serta strategi pengajaran yang kontekstual dan berbasis kearifan lokal. Hasil penelitian menyediakan peta bukti dan rekomendasi bagi pengembangan modul, strategi pembelajaran, dan pelatihan guru berbasis bukti.